2018
DOI: 10.4103/0973-1482.183218
|View full text |Cite
|
Sign up to set email alerts
|

Deglycosylation of wogonoside enhances its anticancer potential

Abstract: Introduction Scutellaria baicalensis is commonly used in Asia as an herbal medicine to treat a variety of ailments, including cancer. Wogonoside, one major constituent of Scutellaria baicalensis, can be primarily converted to wogonin through deglycosylation via enteric microbiome metabolism. Materials and Methods The antiproliferative effects of the glycoside (wogonoside) and its deglycosylated compound (wogonin) on a panel of human cancer cell lines from the most common solid tumors were evaluated using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…Ferulic acid has also been found in many Chinese herbal medicines, such as Ligusticum chuanxiong, Angelica sinensis, Cimicifuga heracleifolia, and Ferula assafoetida . Several biological activities of ferulic acid have been reported such as anti-oxidant, anti-inflammatory, anti-cancer, anti-apoptotic, anti-diabetic, and hepatoprotective. , Emerging evidence suggests that ferulic acid may exert beneficial effects on CRC. , However, the anticancer activity of ferulic acid is comparatively low. , Our previous studies showed that the anticancer activity of some phytochemicals could be enhanced by biotransformation of the human enteric microbiome. , Although ferulic acid could be converted to 4-vinylguaiacol by certain strains of yeast, the metabolism of this compound by the human gut microbiome and the anticancer activity of its metabolites are largely unknown.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Ferulic acid has also been found in many Chinese herbal medicines, such as Ligusticum chuanxiong, Angelica sinensis, Cimicifuga heracleifolia, and Ferula assafoetida . Several biological activities of ferulic acid have been reported such as anti-oxidant, anti-inflammatory, anti-cancer, anti-apoptotic, anti-diabetic, and hepatoprotective. , Emerging evidence suggests that ferulic acid may exert beneficial effects on CRC. , However, the anticancer activity of ferulic acid is comparatively low. , Our previous studies showed that the anticancer activity of some phytochemicals could be enhanced by biotransformation of the human enteric microbiome. , Although ferulic acid could be converted to 4-vinylguaiacol by certain strains of yeast, the metabolism of this compound by the human gut microbiome and the anticancer activity of its metabolites are largely unknown.…”
Section: Introductionmentioning
confidence: 93%
“…16,17 Our previous studies showed that the anticancer activity of some phytochemicals could be enhanced by biotransformation of the human enteric microbiome. 18,19 Although ferulic acid could be converted to 4-vinylguaiacol by certain strains of yeast, 20 the metabolism of this compound by the human gut microbiome and the anticancer activity of its metabolites are largely unknown. Probiotics commonly refer to viable microorganisms that originate from the gut and have beneficial health impacts on the host.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it cannot be excluded that the lower biomass was partly the cause of the higher accumulation of BXs in Lolium shoots. Wogonin and its glucuronide, wogonoside, have various biological effects such as anticancerogenic, anti-inflammatory, and anti-angiogenesis in humans (Wang et al, 2018, Kim et al, 2018, Lin et al, 2012. It is, therefore, very likely that they act as a defense compound against biotic and abiotic stresses in plants.…”
Section: Discussionmentioning
confidence: 99%
“…Wogonoside likely undergoes deglycosylation through enzymatic reactions or microbiome metabolism and covert into wogonin in the rye shoot. It has been reported that deglycosylation of wogonoside enhances its bioactivity by inhibiting the growth of cancer cells (Wang et al, 2018, Yu et al, 2013. Conversion of wogonoside to wogonin in plant shoot may increase their growth inhibitory effects.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, wogonoside induces apoptosis and cell cycle arrest by reducing phospho-mTOR and its downstream target p70S6K and increasing phospho-AMPK in A549 cells, suggesting that the AMPK/mTOR signaling pathway may be involved in the apoptotic activity of wogonoside. A study by Wang et al [ 72 ] did not show any anti-proliferative effects of wogonoside on six cancer cell lines, including NSCLC (DMEM). However, the study observed the anti-proliferative activity on DMEM treated with wogonin (the deglycosylation of wogonoside).…”
Section: Therapeutic Role Of Scutellaria Baicalensis and Their Flavone Compounds In Nicotine-induced Nsclcmentioning
confidence: 99%